2023
DOI: 10.3389/frsus.2022.968886
|View full text |Cite
|
Sign up to set email alerts
|

Addressing plastic bags consumption crises through store monetary and non-monetary interventions in South Africa

Abstract: This research analyses the impact of retailer interventions focusing on the promotion of reusable bags to reduce plastic bag consumption. For this purpose, retail outlet data for March 2018–February 2020 was used. The retail outlet data was analyzed using a panel fixed effects model to evaluate the impact of three treatments on plastic and reusable bag consumption in South Africa. Findings revealed that Treatments 1 (a monetary intervention based on giving reusable bags away for free), and 2 (a non-monetary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The main findings indicate that the majority of the participants perceive plastic bags as an issue, however still use them because it is convenient. Finally, a recent study by Abiola et al (2023) tested monetary and non-monetary interventions on individual behavior. In their study the nonmonetary intervention (a plastic-free month campaign) was more successful than the two monetary interventions tested (one-time giveaway of reusable plastic bags and a subsidy on reusable bags).…”
Section: Literature Review Of Studies On Plastic Bags In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…The main findings indicate that the majority of the participants perceive plastic bags as an issue, however still use them because it is convenient. Finally, a recent study by Abiola et al (2023) tested monetary and non-monetary interventions on individual behavior. In their study the nonmonetary intervention (a plastic-free month campaign) was more successful than the two monetary interventions tested (one-time giveaway of reusable plastic bags and a subsidy on reusable bags).…”
Section: Literature Review Of Studies On Plastic Bags In South Africamentioning
confidence: 99%
“…Altering the type of bags available and standardizing on the least harmful bags through policy measures could reduce the environmental damage caused production (Stafford et al, 2022). However, to enhance utilization of better bags and reduce the overall procurement of new plastic bags, which has to be the ultimate goal, it is imperative to address consumer behavior through environmental education (Otto and Pensini, 2017), prompts (Osbaldiston and Schott, 2012), (social) media campaigns (Borg, 2021;Rapada et al, 2021), community-based initiatives (Moraes et al, 2010), and event-based campaigns, such as plastic-free-months (Abiola et al, 2023).…”
Section: Managerial and Policy Implicationsmentioning
confidence: 99%
“…A wide spectrum of approaches to mitigating the impacts of plastics have been proposed, including the scaling of circular technologies (Ren et al, 2020;Meys et al, 2021;Stegmann et al, 2022;Bachmann et al, 2023;UNEP, 2023c), decarbonization of energy supply (Posen et al, 2017;Zheng and Suh, 2019;Meys et al, 2021), the use of renewable feedstock such as plastic waste, biomass, or captured CO 2 (Shen et al, 2010;Kätelhön et al, 2019;Zheng and Suh, 2019;Meys et al, 2021;Lee et al, 2022;Raj et al, 2022;Stegmann et al, 2022;Bachmann et al, 2023), eliminating or reducing the use of chemicals and polymers of concern and problematic plastic products, minimizing waste generation (Idumah and Nwuzor, 2019;Okan et al, 2019;Chu et al, 2023), and disposal to the environment (Willis et al, 2018;Williams and Rangel-Buitrago, 2019;Schmaltz et al, 2020), economic incentives and behavioral change (Allison et al, 2022;Abiola et al, 2023), and improving reuse and recycling (Keane, 2007;Hopewell et al, 2009;Pacheco et al, 2012;Garcia and Robertson, 2017;Rahimi and García, 2017;Milios et al, 2018;Rosa et al, 2018;British Plastics Federation, 2021;Schwarz et al, 2021;Schyns and Shaver, 2021). Studies indicate that these approaches, in concert, have the potential to reduce plastics discarded to the environment, carbon and other pollutant emissions as well as the dependence of plastic products on fossil fu...…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that individuals who received information about this campaign exhibited reduced plastic consumption compared to those who were not provided with such information. Regarding the context of South Africa, Abiola et al (2023) tested both monetary and non-monetary interventions. Notably, within their investigation, the non-monetary intervention, encompassing a plastic-free monthly campaign, similar to Heidbreder et al (2020) , demonstrated greater effectiveness compared to the two tested monetary interventions, namely, a one-time distribution of reusable plastic bags and a subsidy for reusable bags.…”
Section: Introductionmentioning
confidence: 99%